MOLECULAR MECHANISMS OF NEURODEVELOPMENTAL ALTERATIONS IN PRENATAL AND NEONATAL PERIODS - A. B. Salmina; Yu. K. Komleva; N. V. Kuvacheva; O. L. Lopatina; A. I. Inzhutova; S. M. Cherepanov; N. A. Yauzina; G. A. Morozova; N. A. Malinovskaya; E. A. Pozhilenkova; A. V. Morgun; T. E. Taranushenko; et al. ("Paediatrician" Publishers LLC, 2012)
Review covers current data on molecular mechanisms of brain development in prenatal and early postnatal periods, and their alterations resulting in changes in neuroplasticity and behavioral pattern. Role of oxytocin, mechanisms of neurogenesis in normal conditions, in early-life stress and prenatal stress are in the special focus of the review. Novel approaches to searching the molecular markers and targets for diagnostics and pharmacological correction of neurodevelopmental disorders are discussed.